HIDROSEFALUS DI RSU Dr. SOEDARSO PONTIANAK DALAM MASA 1 JANUARI 2008-31 DESEMBER 2009 - ., Edikta (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background: Hydrocephalus is a central nervous system disorder in form of overvolume of cerebrospinal fluid in the head, either in ventricular system or subarachnoid spaces caused by hydrodynamic disturbance, causing raised intracranial pressure.Objective: giving an epidemiological data on hydrocephalus in West Borneo, especially at dr. Soedarso Pontianak Public Hospital.Method: This study was a descriptive form, that was comparing cases of hydrocephalus: congenital compared to acquired, communicating compared to noncommunicating, symptomatic compared to asymptomatic and the ethiologies of hydrocephalus. The sample taken by non probability, using consecutive sampling. The data derived from medical records, then processed by SPSS (Statistical Product and Service Solution) 17.Result: The result shows the cases of hydrocephalus at dr. Soedarso Public Hospital year 2008 was 35 cases and 45 cases for 2009. Whereby the cases of acquired hydrocephalus higher than congenital, communicating hydrocephalus higher than noncommunicating, symptomatic hydrocephalus higher than asymptomatic.Conclusion: In general the ethiology cant be elucidated through CT scan. Through CT scan, ethiology of hydrocephalus mostly is intracranial tumour.Keywords: hydrocephalus, hydrocephalus cases, hydrocephalus ethiology